Investigation and prediction of noise pollution levels from wind turbines: A case study of Nexif Energy Ben Tre wind power plant, South Vietnam - Nguyen Quoc, Huan; Tran Thien, Cuong; Nguyen Xuan, Cu; Vu Dinh, Tuan; Tran, Minh; Ngo Van, Liem (Vietnam Journal of Earth Sciences, 2021)
In recent years, the demand for electric power in Vietnam has increased at annual growth rates of 10% to 12%, and the challenge is to promote renewable energy sector. One of these sustainable energy sources is to harness energy from the wind through wind turbines (WTs). In fact, more wind power plants in Vietnam are continuously to be built due to the rapidly growing demand of country’s industrialization and modernization process. However, a significant hindrance preventing the widespread use of WTs in Vietnam is the noise they produce, which significantly contributes to the annoyance experienced by residents living near wind farms. The prediction of noise impacts for new wind farms is one of the many aspects of the environmental impact assessment process in Vietnam as well as in the world. In addition, the determination of the 45 dBA noise contour-line is very important because it is the basis for determining the scope of the project impact according to the IFC/WB performance standards and the number of households to be relocated from the project site. The article’s main focus is therefore on the estimation and simulation of the acoustical noise produced by 18 WTs during the operation phase of Nexif Energy Ben Tre wind power plant and the background noise levels at the project site have been performed by using a combination of specific study methods such as environmental modeling (iNoise Pro modeling software), mapping and geographic information systems. The obtained results show the importance of using modeling method in quantifying the noise levels generated from 18 wind turbines of the Nexif Energy Ben Tre wind power plant met IFC standard and Vietnamese regulation on noise during day-time, but did not meet IFC standard on noise during night-time. The level of background noise measured during night-time in the project area also did not meet IFC standard. Therefore, the overall cumulative noise level exceeds the IFC standard for residential area (45 dBA only). In addition, the appropriate solutions to reduce noise levels from WTs are also proposed.